Improving the quality of obstetric care for women with obstructed labour in the national referral hospital in Uganda: lessons learnt from criteria based audit - Kayiga, Herbert; Ajeani, Judith; Kiondo, Paul; Kaye, Dan K. (BMC pregnancy and childbirth, 2016)
Obstructed labour remains a major cause of maternal morbidity and mortality whose complications can be reduced with improved quality of obstetric care. The objective was to assess whether criteria-based audit improves quality of obstetric care provided to women with obstructed labour in Mulago hospital, Uganda. Methods: Using criteria-based audit, management of obstructed labour was analyzed prospectively in two audits. Six standards of care were compared. An initial audit of 180 patients was conducted in September/October 2013. The Audit results were shared with key stakeholders. Gaps in patient management were identified and recommendations for improving obstetric care initiated. Six standards of care (intravenous fluids, intravenous antibiotics, monitoring of maternal vital signs, bladder catheterization, delivery within two hours, and blood grouping and cross matching) were implemented. A re-audit of 180 patients with obstructed labour was conducted four months later to evaluate the impact of these recommendations. The results of the two audits were compared. In-depth interviews and focus group discussions were conducted among healthcare providers to identify factors that could have influenced the audit results. Results: There was improvement in two standards of care (intravenous fluids and intravenous antibiotic administration) 58.9 % vs. 86.1 %; p < 0.001 and 21.7 % vs. 50.5 %; P < 0.001 respectively after the second audit. There was no improvement in vital sign monitoring, delivery within two hours or blood grouping and cross matching. There was a decline in bladder catheterization (94 % vs. 68.9 %; p < 0.001. The overall mean care score in the first and second audits was 55.1 and 48.2 % respectively, p = 0.19. Healthcare factors (negative attitude, low numbers, poor team work, low motivation), facility factors (poor supervision, stock-outs of essential supplies, absence of protocols) and patient factors (high patient load, poor compliance to instructions) contributed to poor quality of care. Conclusion: Introduction of criteria based audit in the management of obstructed labour led to measurable improvements in only two out of six standards of care. The extent to which criteria based audit may improve quality of obstetric care depends on having basic effective healthcare systems in place.